“Bioquímica na escola”: uma proposta didática para a aprendizagem significativa - Silva, Jennifer Alejandra Suárez (2017)
This research entitled "Biochemistry at School: a didactic proposal for meaningful learning" is characterized by being predominantly qualitative, which used as strategy the elaboration and application of a didactic sequence constructed from learning objectives proposed according to the revised Bloom’s Taxonomy. This didactic sequence aimed at reinforcing different abilities of the cognitive domain classified in levels and categories and favoring the meaningful learning of Chemistry contents in the classroom for last year students of high school from a public school of Santa Maria - RS, as well as strengthening the pedagogical and didactic knowledge of teachers in initial formation of Chemistry Degree of the Federal University of Santa Maria. For this, the study was developed in three phases. In the first phase, the aim was to achieve the pedagogical theoretical reference on meaningful and disciplinary learning about the concepts to be approached, such as proteins, carbohydrates and lipids. The second phase was addressed to the theoretical and practical orientation of the teachers in initial formation for the construction of the didactic sequence, approaching different scientific contents in several interventions. The interventions were organized in three thematic workshops based on the Three Pedagogical Moments and the learning objectives proposed for the six levels and categories of knowledge organization of the revised Bloom’s Taxonomy. The third and final step was to apply in the classroom the didactic sequence constructed by the teachers in initial formation and evaluation of the constructed learning. The results of this study were obtained through different data collection instruments, such as: questionnaires, textual productions, didactic sequence activities and the observations and annotations of the researcher, which were analyzed according to the Textual Discourse Analysis. The active participation of teachers in initial formation in studies that provide spaces for articulating university-school, strengthening the pedagogical and didactic knowledge developed during their school and university life, since the teacher needs the use of those in the planning and application of activities, promoting improvements in the teaching process. Furthermore, the results allowed concluding that the application of the didactic sequence favored the meaningful learning of scientific concepts, inasmuch as an evolution was observed in the construction of the knowledge and skills of the cognitive domain of high school students.